EFEKTIVITAS PEMBELAJARAN WEB MENGGUNAKAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) KELAS X SMA - Venny Herawati Simangunsong; Maria Isadora Simangunsong; Bung Heri Parhusip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
This research aims to see whether web-based learning using Google Classroom is effective on the learning outcomes of class X SMA. This type of research conducted in this research is descriptive research. The population in the study are 90 person. From this population, the sample were 30 person which has the same cognitive abilities. Data collection techniques used were tests and observation sheets. Based on the results of research and data processing, the conclusion is that web-based learning using Google Classroom is effective on the learning outcomes of class X SMA